Integrated Strategies for Sustainable Coastal Area Management: A Systematic Literature Review - suhendrinal, Suhendrinal; Insani, Munadia; Syah, Nurhasan; Heldi, Heldi; Catri, Indra; Sholichin, Muhamad (Postgraduate School, Universitas Negeri Padang, 2024)
This study aims to identify and synthesize strategies for managing coastal areas through a systematic literature review. The research adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, focusing on articles published between 2019 and 2023. Data collection utilized Google Scholar and Publish or Perish tools to identify studies related to coastal area management strategies. The inclusion criteria required studies to address coastal management strategies, be written in Indonesian or English, and have been published within the last five years. From an initial pool of 2,000 articles, screening processes narrowed the selection to five articles that met all criteria. The findings underscore the necessity of integrated strategies that balance social, environmental, and economic considerations. Key approaches include empowering local communities, promoting sustainable marine tourism, enhancing disaster resilience through mangrove planting, and fostering stakeholder collaboration. The qualitative synthesis of selected studies emphasizes the significance of adopting participatory methods, such as ICZM, and prioritizing environmental conservation. Successful coastal area management requires harmonizing resource utilization with long-term sustainability to protect ecosystem health and support local livelihoods.